FRESHWATER RESERVOIR EFFECTS IN ARCHAEOLOGICAL CONTEXTS OF SIBERIA AND THE EURASIAN STEPPE. Issue 2 (27th April 2022) - Svyatko, Svetlana V; Reimer, Paula J; Schulting, Rick J; Shevnina, Irina; Logvin, Andrei; Voyakin, Dmitriy; Stobbe, Astrid; Merts, Ilya V; Varfolomeev, Viсtor; Soenov, Vasilii; Tsydenova, Natalia
ABSTRACT: In this paper we evaluate the extent of freshwater reservoir effects (37 samples across 12 locations) and present new data from various archaeological sites in the Eurasian Steppe. Together with a summary of previous research on modern and archaeological samples, this provides the most up-to-date map of the freshwater reservoir offsets in the region. The data confirm previous observations highlighting that FREs are widespread but highly variable in the Eurasian Steppe in both modern and archaeological samples. Radiocarbon dates from organisms consuming aquatic sources, including humans, dogs, bears, aquatic birds and terrestrial herbivores (such as elk feeding on water plants), fish and aquatic mammals, as well as food crusts, could be misleading, but need to be assessed on a case-by-case basis.